Sharing the Fame but Taking the Blame: When Declaring a Single Person Responsible Solves a Free Rider Problem - Li, Xinyu; Schnedler, Wendelin (Management Science)
Teams are formed because input from different people is needed. Providing incentives to team members, however, can be difficult. According to received wisdom, declaring all members responsible fails because real responsibility for team output “diffuses.” But why? Also, why and when does formally declaring one member “responsible” mean that this member can be attributed real responsibility? We offer a model that answers these questions. We identify when jointly declaring a team responsible results in reputation free riding. We show that declaring one person responsible can overcome this problem but only if all other team members are protected from being sanctioned. This paper was accepted by Dorothea Kübler, behavioral economics and decision analysis.